AI cognitive laziness in programming learning among university students. - Alshboul, Hadeel (Journal of Humanities & Social Sciences Studies (JHSSS), 2026)
Artificial intelligence become an essential part in education. In this research we study the impact of Generative Artificial Intelligence GenAi tools on student adoption in programming learning, the data was collected from 105 students how study a programming language in the university the survey include 20 question that is analysis to find the mean, standard deviation and AI dependency Index the result show that the AI Dependency is 3.6 which indicates that student over-reliance on these tools so this will reduce the cognitive effort made by students during learning, we recommend to use these tools to support learning process rather than reduce the critical thinking and cognitive effort.